A digital twin of glimepiride for personalized and stratified diabetes treatment - Elias, Michelle; König, Matthias (Frontiers in Pharmacology, 2025)
IntroductionOptimizing glimepiride therapy for type 2 diabetes (T2DM) is challenged by pronounced inter-individual variability in pharmacokinetics.MethodsWe developed a whole-body physiologically based pharmacokinetic (PBPK) model as a digital twin of glimepiride, enabling systematic evaluation of how patient-specific factors influence drug disposition. Using curated data from 20 clinical studies, the digital twin mechanistically simulates glimepiride’s absorption, distribution, metabolism, and excretion (ADME). It accounts for key determinants of variability including renal and hepatic function, CYP2C9 genotype, and bodyweight.ResultsThe model accurately reproduced observed pharmacokinetics and quantified these factors’ impact on drug exposure. Increased glimepiride exposure was predicted in individuals with hepatic dysfunction or specific CYP2C9 variants, highlighting substantial genetic and physiological effects.DiscussionThis digital twin provides mechanistic insights into pharmacokinetic variability and serves as an in silico platform for exploring individualized dosing and patient stratification strategies, laying the foundation for clinical decision support tools to improve T2DM management.